Viruses and Phytoplasma Reported on the Most Important Vegetable Crops in Syria: A Review - Ismaeil, Faiz; Mando, Jamal; alkhalaf, Mohamad; Kumari, Safaa (Arab Society for Plant Protection, 2023)
Syria is famous for cultivation of many different vegetable crops in most governorates during both winter and summer growing seasons, due to its Mediterranean moderate climate conditions, characterized by a mild winter and a hot dry summer. Vegetables cultivation is a very important sector of the Syrian agriculture, as it represents an important source of income for growers and a source of hard currency through export. The most important vegetables cultivated in Syria are solanaceous crops (potato, tomato, sweet potato, pepper and eggplant), cucurbits (watermelon, melon, cucumber, squash and pumpkin), legumes (broad bean, green bean, green pea and cowpea), cruciferaceous (white cabbage and white cauliflower) and other species such as: green onion, green garlic, lettuce, okra … etc. These vegetable crops are affected by many diseases caused by different causal agents, among them, viruses, viroids and phytoplasmas that are considered the most important pathogens causing many serious and significant diseases. In Syria, during the past forty years, many viruses and few phytoplasmas were investigated and most of them (especially viruses) were recorded on these vegetable crops through many field surveys carried out to evaluate their sanitary status and to determine the economic losses and damages caused by those pathogens. Tens of studies were implemented with the aim of identifying those causal agents on the most important vegetable crops grown in the country and finding out the appropriate approaches for their effective control. Many available and appropriate diagnostic methods such as biological, serological and molecular techniques were used to assess the sanitary status of these crops.